Damage on Earth in the Qur'an: A Study of Thematic Interpretations in Anwar Al Tanzil's Interpretation by Al Baidhawi - Abdullah Akram; Sufian Suri; Wakhdah Faaqih; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
There is a lot of damage that occurs on earth, both on land and in the ocean, this has been explained in the Qur'an. As an ecosystem response to acts of damage committed by humans with the arrival of various natural disasters. There are about 800 verses that talk about the universe and the environment, and man is entrusted as a caliph with the task of maintaining and preserving the natural environment, so that there is a balance between nature and man. Natural Resources that are abundant in the bowels of the earth are intended for humans to meet their needs, so humans are forbidden to make damage. Damage from the natural environment will bring a negative impact on human life as a whole. Global Warming that occurs in some parts of the world is felt by the absence of seasonal regularity, and extreme seasons occur. Even though Allah has given the laws inherent in all creation, and the law works according to the Sunnatullah, but if it is damaged it will have a negative effect. This literary research will answer the impact of environmental damage on humans which has been explicitly explained by Allah through his words collected in the Qur'an. For this reason, the method of analysis used is interpretive comparative between interpretation kittabs. This study took several verses of the Qur'an about the destruction on earth with a mufassir scholar named Al Baidhawi in his book entitled Anwar Wa Al Tanzil Wa Asrar Al Ta'wil. The author takes the relevant verse and takes the essence of the discussion in the book. The findings of this study that environmental damage due to human actions has a multidimensional negative impact that is felt not only by the perpetrators of damage, but also felt by society in general. For this reason, solutions are offered, namely strengthening faith and piety implemented in life, being aware of the importance of the environment, and sustainable natural resource management.